Avaliação do potencial cicatrizante de troxerrutina veiculada em filmes de álcool polivinílico/alginato de sódio/polissacarídeos do Agaricus blazei em modelo de ferida cutânea - Lima, Ana Beatriz Nogueira (2024)
Pressure injury is a public health issue due to the high maintenance costs, supplies, and low adherence to treatment. Therefore, it is necessary to develop pharmaceutical formulations that focus on alternative and biosustainable components, such as phenolic compounds or occlusive, gas-permeable dressings. The present study aimed to formulate, characterize, and evaluate the wound-healing activity of troxerutin (TRX) in polymeric films containing polyvinyl alcohol/sodium alginate/polysaccharides from Agaricus blazei Murill in an excisional skin wound model. Morphology, structure, permeability, and thermal and mechanical properties of the starting materials and films were characterized. For the biological assessment, tissue and slides were characterized by verifying anti-inflammatory and antioxidant activity. Through physicochemical characterizations, it was possible to confirm the structure of the starting materials and their integrity and stability in the formulations. Regarding permeability, it was observed that films containing TRX made the systems more hydrophilic, facilitating gas permeation (69.52 to 72.63 g/h m2). Mechanical tests showed that a higher concentration of the active agent (1% m v -1 ) conferred greater strength and elasticity to the films (29.90 MPa and 2536.1 MPa). Morphological analysis demonstrated a granular and porous surface. An in vitro study of the release profile of the free and film-incorporated active compound showed a better fit to zero-order and Korsmeyer-Peppas mathematical models, respectively. In the in vivo assay, films containing TRX at concentrations from 0.25% to 1.00% were effective in promoting wound healing. Additionally, they showed good epidermis and dermis formation, with greater recovery of damaged tissue due to the formation of blood vessels and the presence of keratinocytes. Antioxidant activity was observed for the film with 0.25% TRX (218.40 μg g -1 ), attributed to the presence of polyphenols. The 1.0% TRX concentration reduced lipid peroxidation (4880 μmol g -1 ) and promoted increased nitrite/nitrate production (540.20 ηmol mg-1 ), as well as reduced production of the pro-inflammatory cytokine IL-1β (2374 ρg mL-1 ). Thus, based on the results obtained, it can be inferred that polyvinyl alcohol/sodium alginate/Agaricus blazei Murill mushroom-based polymeric films containing 1% TRX promote skin healing in the study model and are promising biomaterials for tissue repair.